(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
This study was conducted at the Agricultural Research Station/Rotary for the period (2009-2014). Data was collected from 1375 individual records of Awassi ewes and 1518 births to determine the effect of maternal age, first parity type, and sex on parity type, sex, and birth weight for older ewes. Dams of female lambs were selected to calculate the heritability and genetic correlation between birth weight and weaning weight. Results showed highly significant differences (P < 0.01) between ewe ages in parity type, with single and twin births at 1.5 years of age exceeding other ages by 51.58% and 12.25%, respectively, and decreasing with advancing age. Single births significantly exceeded (P < 0.01) twin births at all ages. For lamb sex, the proportion of male and female births at 1.5 years of age was significantly higher (P < 0.01) at 33.33% and 30.50%, respectively, and decreased to 0.60% and 0.66% with advancing age. The proportion of female births increased after 3.5 years of age at the expense of male births. Results showed a high heritability for birth weight of ewes born in 2009 and born in other years, and a decrease in heritability for the same ewes and the same period for weaning weight. Genetic correlations were very high, while this situation was reversed for ewes born in 2010 and 2011, as well as for weaning weight.